Antibacterial and anticorrosive composition as well as preparation method and application thereof

By combining copper/graphene composite materials with epoxy resin and other materials, antibacterial and anticorrosion compositions are prepared, which solves the problem of insufficient protective performance of existing epoxy coatings in corrosive environments, and achieves efficient antibacterial and anticorrosion effects.

CN119775851AActive Publication Date: 2025-04-08CHINA PETROLEUM & CHEMICAL CORP +1

Patent Information

Application Number
CN202311291660.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-08
Publication Date
2025-04-08
Estimated Expiration
2043-10-08

AI Technical Summary

Technical Problem

The existing epoxy heavy anticorrosion coatings have significantly insufficient protective performance in environments containing corrosive bacteria and erosion conditions, and are not resistant to bacterial corrosion and have poor wear resistance.

Method used

The antibacterial and anticorrosion composition is prepared by combining copper/graphene composite materials, epoxy resins, film forming additives, first organic solvents, fillers and curing agents to enhance its antibacterial properties and corrosion-resistant wear properties.

Benefits of technology

The efficient protection performance of the antibacterial and anticorrosion composition is achieved, including good film formation, adhesion, flexibility, impact resistance, salt spray resistance and antibacterial properties, and solves the problem of insufficient protection of traditional epoxy coatings in corrosive environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775851A_ABST
    Figure CN119775851A_ABST
Patent Text Reader

Abstract

The invention provides an antibacterial and anticorrosive composition as well as a preparation method and application thereof. The antibacterial and anticorrosive composition comprises a copper / graphene composite material, epoxy resin, a coalescing agent, an organic solvent, a filler and a curing agent, and is an antibacterial and anticorrosive coating. The antibacterial anticorrosive composition is good in film-forming property and can be cured at normal temperature, a paint film formed after curing is high in adhesive force, good in flexibility, high in impact resistance, good in salt fog resistance, good in 3.5% NaCl solution corrosion resistance and good in antibacterial property, and the problem that an existing epoxy heavy-duty anticorrosive coating is insufficient in protection performance is solved. The antibacterial anticorrosive paint can be applied to but not limited to the fields of marine ships, coastal infrastructure, petroleum, chemical engineering, electric power, automobiles and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of antibacterial and anticorrosive coatings, and in particular relates to an antibacterial and anticorrosive composition, a preparation method and application thereof. Background Art

[0002] At present, microbial corrosion has become an important factor threatening oil and gas development, and is also an important cause of corrosion failure of underground and surface pipelines. In order to reduce the serious microbial corrosion of the pipeline system caused by fracturing return fluid due to insufficient sterilization of surface water from large-scale hydraulic fracturing during shale gas development, especially the frequent corrosion and perforation of large elbows, horizontal pipes, riser bodies and welds, and the sharp increase in safety risks during oil and gas production. Existing epoxy heavy-duty anti-corrosion coatings often have the disadvantages of high porosity, low hardness, and susceptibility to oxygen, water and chloride ion invasion and damage. At the same time, they are not resistant to bacterial corrosion and have poor wear resistance, resulting in their protection performance being significantly insufficient in environments containing corrosive bacteria and erosion conditions. Therefore, it is urgent to improve traditional epoxy coatings to enhance their antibacterial properties and erosion and wear resistance. Summary of the invention

[0003] The purpose of the present invention is to provide an antibacterial and anticorrosive composition to solve the problem that the protective performance of traditional epoxy coatings in the prior art is obviously insufficient in an environment containing corrosive bacteria and erosion conditions.

[0004] To achieve the above objectives, one of the present inventions provides an antibacterial and anticorrosive composition, which includes a copper / graphene composite material, an epoxy resin, a film-forming aid, a first organic solvent, a filler and a curing agent.

[0005] In the present invention, the copper / graphene composite material is a copper powder particle with a graphene layer grown on the surface; wherein the graphene layer wraps the copper powder particle.

[0006] According to a specific embodiment of the present invention, the copper / graphene composite material is a copper / graphene composite material dispersion.

[0007] According to a specific embodiment of the present invention, the antibacterial and antiseptic composition includes, by mass, 5 to 10 parts of the copper / graphene composite material dispersion, 20 to 45 parts of the epoxy resin, 5 to 15 parts of the first organic solvent, 2.5 to 6 parts of the film-forming aid, 25 to 55 parts of the filler and 10 to 25 parts of the curing agent;

[0008] Preferably, the antibacterial and antiseptic composition comprises, by weight, 10 parts of the copper / graphene composite material dispersion, 20 parts of the epoxy resin, 15 parts of the first organic solvent, 2.8 parts of the film-forming aid, 45 parts of the filler and 10 parts of the curing agent;

[0009] Preferably, the mass of the copper / graphene composite material dispersion is taken as 100%, and the copper / graphene composite material dispersion comprises 20 to 30 wt % of the copper / graphene composite material and 70 to 80 wt % of the second organic solvent;

[0010] Preferably, the mass of the copper / graphene composite material dispersion is calculated as 100%, and the copper / graphene composite material dispersion comprises 23 wt % of the copper / graphene composite material and 77 wt % of the second organic solvent;

[0011] Preferably, the mass of the copper / graphene composite material dispersion is calculated as 100%, and the copper / graphene composite material dispersion comprises 20 to 30 wt % of the styrene-modified copper / graphene composite material and 70 to 80 wt % of a third organic solvent;

[0012] Preferably, the mass of the copper / graphene composite material dispersion is calculated as 100%, and the copper / graphene composite material dispersion includes 23.7 wt % of the copper / graphene composite material modified by styrene and 76.3 wt % of the third organic solvent.

[0013] According to a specific embodiment of the present invention, the epoxy resin is selected from at least one of epoxy resin E20, epoxy resin E21, epoxy resin E44 and epoxy resin E51.

[0014] According to a specific embodiment of the present invention, the first organic solvent, the second organic solvent and the third organic solvent independently include at least one of xylene, n-butanol and cyclohexanone;

[0015] Preferably, the first organic solvent is a mixture of xylene and n-butanol; and / or

[0016] The second organic solvent and the third organic solvent are independently xylene.

[0017] According to a specific embodiment of the present invention, the film-forming aid includes at least one of a dispersant (such as dispersant AFCONA-4010), a defoamer (such as defoamer BKY333) and a leveling agent (such as leveling agent BYK333).

[0018] According to a specific embodiment of the present invention, the filler includes at least one of mica, calcium carbonate and glass powder;

[0019] Preferably, the filler is a mixture of mica and glass powder;

[0020] Preferably, the filler has a particle size of 10 to 40 μm.

[0021] According to a specific embodiment of the present invention, the curing agent includes at least one of polyamide, aromatic amine and alicyclic amine;

[0022] Preferably, the curing agent is curing agent polyamide 651.

[0023] The second aspect of the present invention provides a method for preparing the antibacterial and antiseptic composition according to the first aspect of the present invention, which comprises the following steps:

[0024] A. pretreating the copper / graphene composite material, and then mixing and grinding the copper / graphene composite material with the first organic solvent, epoxy resin, film-forming aid and filler to obtain a mixed slurry;

[0025] B. Mixing the mixed slurry and the curing agent to obtain the antibacterial and antiseptic composition.

[0026] According to a specific embodiment of the present invention, in step A, the pretreatment is to disperse the copper / graphene composite material in the second organic solvent to obtain a copper / graphene composite material dispersion;

[0027] Preferably, the pretreatment is to disperse the copper / graphene composite material and styrene in the third organic solvent, and react to obtain the copper / graphene composite material dispersion.

[0028] According to a specific embodiment of the present invention, the mass ratio of the styrene to the copper / graphene composite material is 1:30; and / or

[0029] The reaction is carried out at room temperature; and / or

[0030] The reaction is modification of the copper / graphene composite material by styrene.

[0031] According to a specific embodiment of the present invention, the mixing temperature in step A is 15 to 60° C.; and / or

[0032] The fineness of the mixed slurry is 10 to 50 μm.

[0033] According to a specific embodiment of the present invention, the copper / graphene composite material is prepared by the following method:

[0034] 1) mixing copper powder and carbon powder and grinding them to obtain a mixed powder;

[0035] 2) placing the mixed powder in a fluidized state, introducing gaseous hydrocarbons, and reacting to obtain the copper / graphene composite material.

[0036] The fluidized state referred to in the present invention specifically refers to the solid fluidized state, that is, solid particles (such as copper powder and carbon powder) are suspended in a moving fluid (such as an inert gas), so that the solid particles are in a fluid-solid contact state with certain characteristics of the fluid.

[0037] According to a specific embodiment of the present invention, in the mixed powder, the mass ratio of the copper powder to the carbon powder is 1:(0.25 to 4);

[0038] Preferably, the mass of the mixed powder is 100 to 400 g.

[0039] According to a specific embodiment of the present invention, the particle size of the copper powder and the particle size of the carbon powder are independently 100 to 500 μm; and / or

[0040] The particle size of the mixed powder is 100 to 300 μm.

[0041] According to a specific embodiment of the present invention, in step 1), the grinding is performed under vacuum conditions; and / or

[0042] First, the mixed powder is placed in a quartz tube, evacuated and heated, and then the step 2) is performed; and / or

[0043] In step 2), an inert gas is introduced to fluidize the mixed powder; and / or

[0044] In step 2), the reaction product obtained by the reaction is cooled to room temperature (25° C.) to obtain the copper / graphene composite material.

[0045] According to a specific embodiment of the present invention, the vacuum degree of the quartz tube is 1×10 -1 Up to 5×10 -1 Pa; and / or the temperature in the quartz tube after heating is 700 to 900° C.;

[0046] Preferably, the flow rate of the inert gas is 500 to 2000 mL / min; and / or

[0047] The flow rate of the gaseous hydrocarbon is 200 to 500 mL / min; and / or

[0048] The reaction time is 30 to 150 min;

[0049] Preferably, the quartz tube is a vertical quartz tube; and / or the inert gas comprises argon and / or helium; and / or

[0050] In step 1), the grinding is performed by vacuum ball milling;

[0051] Preferably, the vacuum degree of the vacuum ball mill is 1×10-3 Up to 3×10 -3 Pa; and / or a rotation speed of 100 to 300 rpm;

[0052] and / or duration is between 20 and 50 minutes;

[0053] Preferably, the gaseous hydrocarbon is at least one of C1 to C4 alkanes, alkenes and alkynes;

[0054] Preferably, the gaseous hydrocarbon is ethylene.

[0055] The use of the antibacterial and antiseptic composition according to one of the present inventions or the antibacterial and antiseptic composition prepared by the method according to the second present invention in antibacterial and antiseptic applications.

[0056] Beneficial effects of the present invention:

[0057] In view of the problem that the existing epoxy heavy-duty anti-corrosion coatings have obviously insufficient protective performance in environments containing corrosive bacteria and erosion conditions, the present invention provides an antibacterial anti-corrosion composition, a preparation method and application thereof. The antibacterial anti-corrosion composition comprises a copper / graphene composite material, an epoxy resin, a film-forming aid, a first organic solvent, a filler and a curing agent, and is an antibacterial anti-corrosion coating. The antibacterial anti-corrosion composition provided by the present invention has good film-forming properties (the paint film formed after the antibacterial anti-corrosion composition is cured has a smooth appearance and no particles or grooves), can be cured at room temperature, and the paint film formed after curing has strong adhesion (the adhesion can reach level 0, the cut edge is very smooth, and none of the squares in the grid are peeled off), good flexibility (no cracking or peeling is observed when using an axis with a minimum diameter of 2mm), strong impact resistance (no cracks, wrinkles or peeling were observed in three experiments, and the maximum height was 40 to 50cm), and good salt spray resistance (salt spray resistance can reach 1200h, and no blistering, rust or rust from scratches occurs). The invention has good corrosion resistance to 3.5% NaCl solution (no gloss loss, discoloration, rust, blistering, shedding and cracking within 1000 hours) and good antibacterial property (the antibacterial property can reach level 1, with antibacterial property of not less than 99% and antibacterial durability of not less than 95%), which solves the problem of insufficient protective performance of existing epoxy heavy-duty anticorrosion coatings, and the preparation method is simple. The invention can be used as an antibacterial anticorrosion coating in fields including but not limited to marine ships, coastal infrastructure, petroleum, chemical industry, electric power, automobiles, etc., especially in the antibacterial and anticorrosion of ground gathering and transportation pipelines in oil and gas fields and substrates of refining and chemical equipment. BRIEF DESCRIPTION OF THE DRAWINGS

[0058] Figure 1 This is a surface electron scanning electron micrograph of a paint film formed by the antibacterial and anticorrosive composition prepared in Example 3;

[0059] Figure 2 This is a surface electron scanning electron micrograph of a paint film formed by the antibacterial and anticorrosive composition prepared in Example 2;

[0060] Figure 3 This is a corrosion photograph of the paint film formed by the antibacterial and anticorrosive composition prepared in Example 3 after 1200 hours of salt spray resistance test;

[0061] Figure 4 This is the AC impedance spectrum change curve of the paint film formed by the antibacterial and antiseptic composition prepared in Example 3 after being immersed in a 3.5% NaCl solution for 50 days, wherein the thickness of the paint film is 90 μm. DETAILED DESCRIPTION

[0062] The present invention will be further described below in conjunction with examples, but the examples of the present invention are only exemplary descriptions, and the implementation methods do not constitute limitations of the present invention under any circumstances.

[0063] The room temperature below refers to 25°C.

[0064] Preparation of copper / graphene composites

[0065] Example 1

[0066] 1) 100 g of copper powder with a particle size of 200 μm and 150 g of carbon powder with a particle size of 300 μm were placed in a container and stirred and mixed, and then placed in a planetary vacuum ball mill for vacuum ball milling. The vacuum degree of the ball milling was 1.510 -3 Pa, the rotation speed is 200 rpm, and the ball milling time is 35 min, and then the mixed powder with an average particle size of 150 μm is obtained;

[0067] 2) 300 g of the mixed powder prepared according to the method in step 1) was placed in a vertical quartz tube near the air inlet and vacuumed to 1×10 -1 Pa, start the heating program, and when heated to 800°C, introduce protective gas argon at a flow rate of 1500mL / min until the mixed powder is in a fluidized state, and then introduce 330mL / min of ethylene to grow graphene. The reaction time is 120min. After the reaction is completed, turn off the gas and then cool to room temperature to obtain a copper / graphene composite material.

[0068] Preparation of antibacterial and antiseptic compositions

[0069] Example 2

[0070] A. Pretreatment of copper / graphene composite material: At room temperature, weigh 15 g of the copper / graphene composite material prepared in Example 1 and add it to 50 g of xylene for ultrasonic dispersion. The ultrasonic time is 2 h and the ultrasonic power is 600 W to obtain a copper / graphene composite material dispersion.

[0071] Prepare a mixed slurry: take 10g of copper / graphene composite material dispersion, add 20g of epoxy resin E21, 10g of xylene, 5g of n-butanol, 30g of mica powder with an average particle size of 30μm, 15g of glass powder with an average particle size of 30μm, 0.5g of leveling agent BYK333, 0.8g of defoaming agent BKY333 and 1.5g of dispersant AFCONA-4010, and stir at room temperature with a stirrer at a speed of 2000r / min for 30min to obtain a mixed slurry;

[0072] B. Grind the obtained mixed slurry in a grinder for 2 hours until the fineness is 50 μm, add 10 g of curing agent polyamide 651, stir and mix evenly to obtain an antibacterial and antiseptic composition.

[0073] Example 3

[0074] A. Pretreatment of copper / graphene composite material: at room temperature, weigh 15 g of the copper / graphene composite material prepared in Example 1 and 0.5 g of styrene, add them into 50 g of xylene for ultrasonic dispersion, the ultrasonic time is 2 h, the ultrasonic power is 600 W, during the ultrasonic dispersion process, styrene and copper / graphene composite material react, the modification of copper / graphene composite material by styrene is completed, and copper / graphene composite material dispersion is obtained;

[0075] Prepare a mixed slurry: take 10g of copper / graphene composite material dispersion, add 20g of epoxy resin E20, 10g of xylene, 5g of n-butanol, 30g of mica powder with an average particle size of 30μm, 15g of glass powder with an average particle size of 30μm, 0.5g of leveling agent BYK333, 0.8g of defoaming agent BKY333 and 1.5g of dispersant AFCONA-4010, and stir at room temperature with a stirrer at a speed of 2000r / min for 30min to obtain a mixed slurry;

[0076] B. Grind the obtained mixed slurry in a grinder for 2 hours until the fineness is 50 μm, add 10 g of curing agent polyamide 651, stir and mix evenly to obtain an antibacterial and antiseptic composition.

[0077] Example 4

[0078] A. Pretreatment of copper / graphene composite material: at room temperature, weigh 15 g of the copper / graphene composite material prepared in Example 1 and 0.5 g of styrene, add them into 50 g of xylene for ultrasonic dispersion, the ultrasonic time is 2 h, the ultrasonic power is 600 W, during the ultrasonic dispersion process, styrene and copper / graphene composite material react, the modification of copper / graphene composite material by styrene is completed, and copper / graphene composite material dispersion is obtained;

[0079] Prepare a mixed slurry: take 10g of copper / graphene composite material dispersion, add 20g of epoxy resin E44, 10g of xylene, 5g of n-butanol, 30g of mica powder with an average particle size of 10μm, 15g of glass powder with an average particle size of 40μm, 0.5g of leveling agent BYK333, 0.8g of defoaming agent BKY333 and 1.5g of dispersant AFCONA-4010, stir at 15°C with a stirrer at a speed of 2000r / min for 30min to obtain a mixed slurry;

[0080] B. Grind the obtained mixed slurry in a grinder for 12 hours until the fineness is 10 μm, add 5 g of curing agent polyamide 651 and 5 g of alicyclic amine, stir and mix evenly to obtain an antibacterial and antiseptic composition.

[0081] Example 5

[0082] A. Pretreatment of copper / graphene composite material: at room temperature, weigh 15 g of the copper / graphene composite material prepared in Example 1 and 0.5 g of styrene, add them into 50 g of xylene for ultrasonic dispersion, the ultrasonic time is 2 h, the ultrasonic power is 600 W, during the ultrasonic dispersion process, styrene and copper / graphene composite material react, the modification of copper / graphene composite material by styrene is completed, and copper / graphene composite material dispersion is obtained;

[0083] Prepare a mixed slurry: take 10g of copper / graphene composite material dispersion, add 20g of epoxy resin E51, 10g of xylene, 5g of n-butanol, 15g of mica powder with an average particle size of 40μm, 30g of glass powder with an average particle size of 10μm, 0.5g of leveling agent BYK333, 0.8g of defoaming agent BKY333 and 1.5g of dispersant AFCONA-4010, stir at 60°C with a stirrer at a speed of 2000r / min for 30min to obtain a mixed slurry;

[0084] B. Grind the obtained mixed slurry in a grinder for 8 hours until the fineness is 30 μm, add 10 g of curing agent polyamide 651, stir and mix evenly to obtain an antibacterial and antiseptic composition.

[0085] Comparative Example 1

[0086] A. Preparation of mixed slurry: 20g epoxy resin E20, 10g xylene, 5g n-butanol, 40g mica powder with an average particle size of 30μm, 15g glass powder with an average particle size of 30μm, 0.5g leveling agent BYK333, 0.8g defoamer BKY333 and 1.5g dispersant AFCONA-4010 were taken, and stirred at room temperature with a stirrer at a speed of 2000r / min for 30min to obtain a mixed slurry;

[0087] B. Grind the obtained mixed slurry in a grinder for 2 hours until the fineness is 50 μm, add 10 g of curing agent polyamide 651, stir and mix evenly to obtain an antibacterial and antiseptic composition.

[0088] Test Example 1

[0089] The appearance, adhesion, flexibility, impact resistance, salt spray resistance, corrosion resistance to 3.5% NaCl solution and antibacterial properties of the paint films obtained after film formation of the antibacterial and anticorrosive compositions prepared in Examples 2 to 5 and Comparative Example 1 were measured to evaluate the performance of the antibacterial and anticorrosive compositions as antibacterial and anticorrosive coatings.

[0090] The specific method is as follows:

[0091] ⅰ Preparation of paint film

[0092] The steel substrate is sandblasted to remove oxides, adsorbents and other impurities on the surface thereof, and then the antibacterial and anticorrosive composition prepared in any one of Examples 2 to 5 and Comparative Example 1 is sprayed on the treated steel substrate, and naturally dried for 24 hours to form a paint film with an average thickness of 90 μm on the steel substrate;

[0093] According to the above method, the antibacterial and antiseptic compositions prepared in Examples 2 to 5 and Comparative Example 1 were used to prepare paint films for later use.

[0094] ⅱ Paint film appearance

[0095] 1) Using a visual inspection method, observe whether the appearance of the paint film prepared by the antibacterial and anticorrosive compositions prepared in Examples 2 to 5 and Comparative Example 1 is smooth. The specific results are shown in Table 1;

[0096] 2) The surface morphology of the paint film prepared by the antibacterial and anticorrosive compositions prepared in Example 3 and Example 2 was observed using a scanning electron microscope. Figure 1 , Figure 2 .

[0097] ⅲ Paint film adhesion

[0098] According to the method specified in the international standard ISO 2409, the adhesion grade of the paint film formed by the antibacterial and anticorrosive composition on the steel substrate was measured. The specific results are shown in Table 1.

[0099] ⅳ Paint film flexibility

[0100] According to the method specified in the national standard GB / T 6742, the flexibility of the paint film formed by the antibacterial and anticorrosive composition on the steel substrate was measured. The specific results are shown in Table 1.

[0101] ⅴPaint film impact resistance

[0102] According to the method specified in the national standard GB / T 1732, the impact resistance of the paint film formed by the antibacterial and anticorrosive composition on the steel substrate was measured. The specific results are shown in Table 1.

[0103] ⅵSalt spray resistance

[0104] According to the method specified in the national standard GB / T 1771, the salt spray resistance of the paint film formed by the antibacterial and anticorrosive composition on the steel substrate was determined. The specific results are shown in Figure 3 , Table 1.

[0105] ⅶ Corrosion resistance to 3.5% NaCl solution

[0106] According to the method specified in the national standard GB / T 10834, the corrosion resistance of the paint film formed by the antibacterial and anticorrosive composition on the steel substrate to 3.5% NaCl solution was measured. The specific results are shown in Figure 4 , Table 1.

[0107] ⅷ Antibacterial properties

[0108] According to the method specified in the national standard GB / T 21866, the antibacterial properties of the paint film formed by the antibacterial and anticorrosive composition on the steel substrate were measured. The specific results are shown in Table 1.

[0109] Table 1. Properties of the paint film formed by the antibacterial and antiseptic composition

[0110] Paint film properties Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Appearance smooth smooth smooth smooth smooth Adhesion Level 1 Level 0 Level 1 Level 0 Level 1 Flexibility 2mm 2mm 2mm 2mm 2mm Impact resistance 40cm 50cm 50cm 40cm 40cm Salt spray resistance (h) 650 1200 1100 1100 600 Resistance to 3.5% NaCl solution (h) 700 1000 950 900 700 Antimicrobial Level 2 Level 1 Level 1 Level 1 Not antibacterial

[0111] Combination Figures 1 to 4 The data in Table 1 are used to analyze the appearance, adhesion, flexibility, impact resistance, salt spray resistance, corrosion resistance to 3.5% NaCl solution and antibacterial properties of the paint films. (1) Appearance: Table 1 shows that the appearance of the paint films formed by the antibacterial and anticorrosive compositions prepared in Examples 2 to 5 are all smooth, and Figure 1 and Figure 2It is also shown that under the scanning electron microscope, the surface flatness of the paint film formed by the antibacterial anticorrosive composition prepared in Example 3 and Example 2 is good, indicating that the antibacterial anticorrosive composition prepared in Examples 2 to 5 has good film-forming performance. (2) Adhesion: The adhesion of the paint film formed by the antibacterial anticorrosive composition prepared in Examples 2 to 5 is between level 0 and level 1, and the adhesion of the paint film formed by the antibacterial anticorrosive composition prepared in Examples 3 and 5 is level 0 (i.e., the cut edge is very smooth, and none of the square blocks in the grid peels off), indicating that the antibacterial anticorrosive composition prepared in Examples 2 to 5 has good adhesion after film formation and is not easy to fall off from the substrate. (3) Flexibility: The paint film formed by the antibacterial anticorrosive composition prepared in Examples 2 to 5 has good flexibility, and there is no cracking or peeling when tested using an axis with a minimum diameter (i.e., 2 mm). (4) Impact resistance: The paint films formed by the antibacterial and anticorrosive compositions prepared in Examples 2 to 5 had no cracks, wrinkles or peeling observed in three tests, with a maximum height of 40 to 50 cm. Among them, the paint films formed by the antibacterial and anticorrosive compositions prepared in Examples 3 and 4 had no cracks, wrinkles or peeling observed in three tests, with a maximum height of 50 cm, showing strong impact resistance. (5) Salt spray resistance: The paint films formed by the antibacterial and anticorrosive compositions prepared in Examples 2 to 5 were salt spray resistant for 650 to 1200 hours, without blistering, rust or rust spreading from scratches, showing good salt spray resistance; Figure 3 The following is a photograph of the paint film formed by the antibacterial and anticorrosive composition prepared in Example 3 after being subjected to a salt spray resistance test for 1200 hours. It can be seen that there is no blistering on the surface of the paint film, no corrosion occurs in areas other than the cross scratches, and the rust at the cross scratches does not spread from the scratches to the surrounding areas, indicating good salt spray resistance. Compared with Example 3, the paint film formed by the antibacterial and anticorrosive composition prepared in Comparative Example 1 is resistant to salt spray for 600 hours, which is 600 hours shorter than that in Example 3, and the salt spray resistance is significantly reduced. (6) Resistance to corrosion by 3.5% NaCl solution: The paint film formed by the antibacterial and anticorrosive composition prepared in Examples 2 to 5 is resistant to corrosion by 3.5% NaCl solution for 700 to 1000 hours, and no loss of gloss, discoloration, rust, blistering, shedding or cracking occurs within 700 to 1000 hours, indicating good resistance to corrosion by 3.5% NaCl solution; Figure 4The AC impedance spectrum change curve of the paint film with a thickness of 90 μm formed by the antibacterial and anticorrosive composition prepared in Example 3 after being immersed in a 3.5% NaCl solution for 50 days shows that the impedance modulus of the paint film slowly decreases with the extension of the immersion time, and the radius of the capacitive reactance arc gradually decreases, indicating that the paint film formed by the antibacterial and anticorrosive composition prepared in Example 3 has good stability and resistance to corrosion by 3.5% NaCl solution. Compared with Example 3, the paint film formed by the antibacterial and anticorrosive composition prepared in Comparative Example 1 has a corrosion resistance of 700 hours to 3.5% NaCl solution, which is 300 hours shorter than that in Example 3, and the corrosion resistance to 3.5% NaCl solution is greatly reduced. (7) Antibacterial property: The paint film formed by the antibacterial antiseptic composition prepared in Examples 3 to 5 has an antibacterial property of Grade 1, an antibacterial property of not less than 99%, and an antibacterial durability of not less than 95%, and is suitable for places with high requirements for antibacterial property. The paint film formed by the antibacterial antiseptic composition prepared in Example 2 has an antibacterial property of Grade 2, an antibacterial property of not less than 90%, and an antibacterial durability of not less than 85%, and is suitable for places with requirements for antibacterial property. Compared with Example 3, the paint film formed by the antibacterial antiseptic composition prepared in Comparative Example 1 has no antibacterial property and cannot be used in places with requirements for antibacterial property.

[0112] From the formula point of view, compared with Example 3, Comparative Example 1 replaces 10g of copper / graphene composite material dispersion with an equal mass of mica powder, which shows that the adhesion and impact resistance of the paint film formed by the antibacterial and anticorrosive composition prepared in Comparative Example 1 are slightly lower than those in Example 3, and the salt spray resistance and corrosion resistance of 3.5% HCl solution are much lower than those in Example 3. In addition, the antibacterial and anticorrosive composition prepared in Comparative Example 1 does not have antibacterial properties and cannot be used in places where antibacterial properties are required, which limits its scope of application.

[0113] Although the present invention has been described with reference to specific embodiments, it will be appreciated by those skilled in the art that various changes may be made without departing from the true spirit and scope of the present invention. In addition, the subject matter, spirit and scope of the present invention may be varied to accommodate specific situations, materials, material combinations and methods. All of these changes are included within the scope of the claims of the present invention.

Claims

1. An antibacterial and anticorrosive composition comprising a copper / graphene composite material, an epoxy resin, a film-forming aid, a first organic solvent, a filler and a curing agent.

2. The antibacterial and antiseptic composition according to claim 1, characterized in that: The copper / graphene composite material is a copper / graphene composite material dispersion.

3. The antibacterial and antiseptic composition according to claim 2, characterized in that: The antibacterial and antiseptic composition comprises, by weight, 5 to 10 parts of the copper / graphene composite material dispersion, 20 to 45 parts of the epoxy resin, 5 to 15 parts of the first organic solvent, 2.5 to 6 parts of the film-forming aid, 25 to 55 parts of the filler and 10 to 25 parts of the curing agent; Preferably, the mass of the copper / graphene composite material dispersion is taken as 100%, and the copper / graphene composite material dispersion comprises 20 to 30 wt % of the copper / graphene composite material and 70 to 80 wt % of the second organic solvent; Preferably, taking the mass of the copper / graphene composite material dispersion as 100%, the copper / graphene composite material dispersion comprises 20 to 30 wt % of the styrene-modified copper / graphene composite material and 70 to 80 wt % of a third organic solvent.

4. The antimicrobial and antiseptic composition according to any one of claims 1 to 3, characterized in that: The epoxy resin is selected from at least one of epoxy resin E20, epoxy resin E21, epoxy resin E44 and epoxy resin E51.

5. The antibacterial and antiseptic composition according to claim 3, characterized in that: The first organic solvent, the second organic solvent and the third organic solvent independently include at least one of xylene, n-butanol and cyclohexanone.

6. The antimicrobial and antiseptic composition according to any one of claims 1 to 5, characterized in that: The film-forming aid includes at least one of a dispersant, a defoamer and a leveling agent.

7. The antimicrobial and antiseptic composition according to any one of claims 1 to 6, characterized in that: The filler includes at least one of mica, calcium carbonate and glass powder.

8. The antimicrobial and antiseptic composition according to any one of claims 1 to 7, characterized in that: The curing agent includes at least one of polyamide, aromatic amine and alicyclic amine.

9. A method for preparing the antimicrobial and antiseptic composition according to any one of claims 1 to 8, comprising the following steps: A. pretreating the copper / graphene composite material, and then mixing and grinding the copper / graphene composite material with the first organic solvent, epoxy resin, film-forming aid and filler to obtain a mixed slurry; B. Mixing the mixed slurry and the curing agent to obtain the antibacterial and antiseptic composition.

10. The method according to claim 9, characterized in that In step A, the pretreatment is to disperse the copper / graphene composite material in the second organic solvent to obtain a copper / graphene composite material dispersion; Preferably, the pretreatment is to disperse the copper / graphene composite material and styrene in the third organic solvent, and react to obtain the copper / graphene composite material dispersion.

11. The method according to claim 10, characterized in that The mass ratio of the styrene to the copper / graphene composite material is 1:30; and / or The reaction was carried out at room temperature.

12. The method according to any one of claims 9 to 11, characterized in that The mixing temperature in step A is 15 to 60° C.; and / or The fineness of the mixed slurry is 10 to 50 μm.

13. Use of the antibacterial and antiseptic composition according to any one of claims 1 to 8 or the antibacterial and antiseptic composition prepared by the method according to any one of claims 9 to 12 in antibacterial and antiseptic applications.

Citation Information

Patent Citations

  • Storage device based on graphene oxide / polystyrene / gold nanoparticle composite and preparation method thereof

    CN104952900A

  • Graphene / copper composite material and preparation and application thereof

    CN109112504A

  • High-performance graphene conductive anticorrosive paint and preparation method thereof

    CN111826081A

Cited By

  • Corrosion-resistant environment-friendly coating as well as preparation method and application thereof

    CN120383864A